Phonocardiography based pulse wave velocity system for non-occlusive assessment of arterial stiffness - Margain, T. Corina; Powell, Emily; Clark, Alexandra; Bush, Adam (Frontiers in Cardiovascular Medicine, 2025)
Arterial stiffness is strongly associated with vascular aging and pathology and can be assessed in many ways. Existing devices for measuring central arterial stiffness, such as carotid-femoral pulse wave velocity (PWV), are limited by high costs and the need for specialized expertise, limiting widespread clinical adoption. This study introduces a semi- and non-occlusive PWV measurement system using phonocardiography (PCG) and plethysmography (PPG) and a single femoral pressure cuff, aiming to address these limitations. We conducted a study comparing a semi-occlusive (carotid-femoral PWV) and a non-occlusive (carotid-toe PWV) PCG-based PWV measurements across a cohort of 63 volunteers, as compared to literature reference PWV values. Results demonstrated strong correlations between our PCG-based PWV measures (PWVcarotid−femoral: 8.42 ± 3.99 m/s vs. PWVcarotid−toe: 10.62 ± 3.86 m/s) with age as a significant predictor (PWVcarotid−femoral: r2 = 0.45; PWVcarotid−toe: r2 = 0.28, p < 0.05). Ultrasound measured distensibility assessments confirmed the reliability of our PCG approach in reflecting central arterial stiffness dynamics, particularly at the aortic level. Test–retest reliability analyses yielded high intraclass correlation coefficients (0.75 ≤ ICC ≤ 90), indicating robust repeatability of our method. This study highlights the feasibility and accuracy of our low-cost, semi and non-occlusive PWV measurement systems to enhance accessibility in arterial stiffness assessments, potentially easing cardiovascular risk stratification.